2019
DOI: 10.1186/s13073-019-0693-z
|View full text |Cite
|
Sign up to set email alerts
|

An epigenome-wide association study of sex-specific chronological ageing

Abstract: BackgroundAdvanced age is associated with cognitive and physical decline and is a major risk factor for a multitude of disorders. There is also a gap in life expectancy between males and females. DNA methylation differences have been shown to be associated with both age and sex. Here, we investigate age-by-sex differences in blood-based DNA methylation in an unrelated cohort of 2586 individuals between the ages of 18 and 87 years, with replication in a further 4450 individuals between the ages of 18 and 93 yea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
99
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 51 publications
17
99
3
Order By: Relevance
“…Finally, we searched for those probes displaying different DNA methylation trajectories in males and females during aging. We identified 8 probes having age-by-sex interaction, 2 of which were recently reported by McCartney et al in an independent dataset [32]. In particular we found that FIGN gene, which encodes for an ATP-dependent microtubule severing enzyme which catalyzes internal breaks in microtubules, included both probes from the saDMPs list and displaying age-by-sex interactions.…”
Section: I) Sadmps In Healthy Subjects Of Different Ages and Populatisupporting
confidence: 61%
See 3 more Smart Citations
“…Finally, we searched for those probes displaying different DNA methylation trajectories in males and females during aging. We identified 8 probes having age-by-sex interaction, 2 of which were recently reported by McCartney et al in an independent dataset [32]. In particular we found that FIGN gene, which encodes for an ATP-dependent microtubule severing enzyme which catalyzes internal breaks in microtubules, included both probes from the saDMPs list and displaying age-by-sex interactions.…”
Section: I) Sadmps In Healthy Subjects Of Different Ages and Populatisupporting
confidence: 61%
“…Meta-analysis resulted in 8 CpG probes whose methylation showed different aging trajectories according to sex (Supplementary File 4). Two of these CpG sites were previously identified as having age-by-sex interaction in whole blood [32], and the most significant CpG site (cg18834375) mapped within FIGN gene, that was the top ranker also in the list of saDMPs and included multiple CpG sites showing sex-and age-dependent methylation (cg01620164, cg19156483, cg10864319, cg18834375, cg15259986 and cg03878133).…”
Section: Identification Of Sex-and Age-associated Differentially Methmentioning
confidence: 99%
See 2 more Smart Citations
“…The IEAA-associated locus on chromosome 3 (lead SNP rs1047210) colocalized with an eQTL for TRIM59. DNA methylation levels at TRIM59 have been robustly associated with chronological age and its expression has been noted in multiple cancers [53,54,55,56,57].…”
Section: Mendelian Randomisation Between Age Acceleration Phenotypes mentioning
confidence: 99%